Advances in food science and technology - Thomas, Sabu.; Iturriaga, Laura B.; Ribotta, Pablo Daniel; P. M., Visakh (New York : Wiley, 2013)
This book comprehensively reviews research on new developments in all areas of food chemistry/science and technology. It covers topics such as food safety objectives, risk assessment, quality assurance and control, good manufacturing practices, food process systems design and control and rapid methods of analysis and detection, as well as sensor technology, environmental control and safety. The book focuses on food chemistry and examines chemical and mechanical modifications to generate novel properties, functions, and applications.
5.3.2 Sensory Properties of Food5.4 Postharvest Storage and Processing; 5.4.1 Bioactive Compounds Postharvest; 5.5 Conclusion; Acknowledgements; References; 6 Food: Production, Properties and Quality; 6.1 Introduction; 6.2 Food Production; 6.3 Factors Affecting Production and Improvement of Food; 6.3.1 Soil and Climate; 6.3.2 Population and Income Per Capita; 6.3.3 Technology; 6.3.4 Plant Source Foods; 6.3.5 Animal Source Foods; 6.4 Food Properties; 6.5 Food Quality; References.
Includes bibliographical references and index.
Print version record.
Keywords: Food -- Analysis; Food industry and trade; COOKING -- General; TECHNOLOGY & ENGINEERING -- Food Science; Food -- Analysis; Food industry and trade; Aliments -- Anàlisi; Aliments -- Indústria i comerç; Llibres electrònics; Electronic books